Prediction of the motion of spacecraft in oskulyuvalnyh cells by differential-teylorivskyh transformations - Ракушев, М.Ю.; Завада, А.А.; Ковбасюк, С.В. (Proceedings of National Aviation University (archive), 2009)
The numerical-analytical computing scheme of integration of the differential equation of motion of space vehicle is offered in osculating elements, which is developed on a basis of Taylor differential transformations. In the model of motion of space vehicle indignations from the central field to 8´8 harmonics of decomposition of a geopotential of the Earth abreast on spherical functions and force of aerodynamic resistance of atmosphere are considered at static model of density of atmosphere. Comparison on accuracy of forecasting of movement of a space vehicle with regular domestic program complexes of ballistic navigational support of flights of space vehicles is spent.